Alternative treatment for anxiety based on the medicinal plant Melissa Officinalis (lemon balm) - a literature review (Research, Society and Development, 2021)
Brazil is considered one of the countries with the highest rate of people with anxiety disorders in the world. A fundamental characteristic of anxiety disorder is the excessive worry that continues to generate a series of physical symptoms associated with autonomic hyperactivity and muscular tension. The plant Melissa officinalis L., popularly known as true lemon balm is a plant belonging to the Lamiaceae family, which originates in Asia and Europe. It has a very characteristic odor of lemon, being widely used to control various nervous crises, anxiety and hysterics, it has the function of controlling emotions through its activity, tranquilizer and inducing sleep. This study aimed to analyze studies regarding the action of Melissa officinalis and verify if it can be seen as an alternative for the treatment of anxiety. The chemical composition of Melissa officinalis L. is essentially composed of terpenes and phenylpropanoids, which are responsible for the herbal action, its essential oil is obtained by hydrodistillation, its low yield makes it one of the most valuable essential eyes. Lemon balm has drug interactions with central nervous system (CNS) depressants, sedatives, antidepressants, stimulants, narcotic analgesics, muscle relaxants and antihistamines. Melissa officinalis L. is used in the production of herbal medicines, as an alternative treatment to anxiety and sleep disorders, with minimal adverse effects and relative safety of use. It can be observed that Melissa has a therapeutic effect on anxiety, resulting from its pharmacological activities.